The Mediating Role of Attitude in Influencing Consumer Purchase Intention Towards Online Apparel Shopping in Malaysia. - Selvi @ Kausiliha, Vijayan; Hock, Oo Yu (2022)
Online apparel shopping had been growing steadily in Malaysia over the decade. Regardless, the aspects of purchase intention are not well researched, and a holistic framework remains limited. Considering the potential of apparel shopping, this study was conducted to develop an integrated framework and to understand the role of attitude as a mediator using baseline models such as the Technology Acceptance Model (TAM) and Theory of Planned Behaviour (TPB). Using purposive sampling, this study retrieved 314 responses through a self-administered questionnaire from online apparel shoppers in Malaysia. The hypotheses were tested using PLSSEM. Conclusively, perceived risk, web experience, pricing, utilitarian, hedonic, and products and service attributes demonstrated a significant relationship towards attitude. Direct relationships were also present between pricing, utilitarian, hedonic, convenience and online apparel purchase intention (OAPI). Interestingly, attitude was found to mediate all variables towards purchase intention except for convenience. The findings contribute academically to marketing and online apparel literature in the Malaysian context. With these innovative insights, online marketers and online apparel business owners can better comprehend online buyers' interest to purchase.